Effect of intercropping chili (Capsicum annuum L.) with onion (Allium cepa L.) in sandy regosol - Brintha, I; Seran, Thayamini H (Bangladesh Journal of Agricultural Research, 2012)
Bangladesh J. Agril. Res. 37(3): 547-550, September 2012 DOI: http://dx.doi.org/10.3329/bjar.v37i3.12132